Maltrato físico y psicológico familiar frente a la falta de motivación y rendimiento en los estudiantes. - López, Ana V. (2022)
The main objective of this research was to determine if physical and psychological abuse affect the lack of motivation and low performance in the students of the García Moreno Educational Unit, Carchi Province, Bolívar Canton, school period 2021-2022. The study was opened with a sample of 110 students from the initial, basic elementary, basic middle, basic upper and high school levels, a research design was taken with a quantitative, descriptive approach. The study concludes that in the institution that is the subject of the study, if there are high rates of abuse suffered by students within the homes, compared to a minimum percentage that has not had any type of punishment, it can be added that 92.7% of students who receive mistreatment do not pay attention in class and present behavioral alterations, so their performance and behavior is affected considerably during the learning process. Also, it was possible to identify that 87.27 of the students of the García Moreno Educational Unit are not frequently motivated in class. By applying statistical analysis of Spearman's Rho connections, it was possible to determine that family physical and psychological abuse affects the lack of motivation and school performance of the students of the García Moreno Educational Unit, in a positive and strong way, since the two-sided significance is .000.